Usual nutrient intake adequacy among young, rural Zambian children - Caswell, Bess L.; Talegawkar, Sameera; Siamusantu, Ward; West, Keith; Palmer, Amanda (Cambridge University Press, 2018)
Inadequate nutrient intakes put children at risk for impaired growth and development. We described diet, usual intakes of energy and macro- and micronutrients and prevalence of nutrient intake adequacies among 4–8-year-old Zambian children. Children not yet in school and living in Mkushi District, Central Province, Zambia were enrolled into an efficacy trial of pro-vitamin A biofortified maize. Children in the non-intervened arm were included in this analysis (n 202). Dietary intake data were collected by tablet-based 24-h recall on a monthly basis over the 6-month trial. Observed nutrient intakes were derived from reported food quantities, standard recipes and food composition tables. Usual nutrient intake distributions were modelled based on observed intakes. Prevalence of inadequacy was estimated by comparing the usual nutrient intake distribution to the nutrient requirement distribution. Frequency and quantity of consumption of commonly reported foods were described and key sources of energy and nutrients were identified. Median usual energy intake was 6422 kJ/d (1535 kcal/d). Most childrens’ macronutrient intakes fell within recommended ranges (74–98 %). Estimated prevalences of inadequate intakes of Fe, folate, vitamin B12 and Ca were 25, 57, 76 and >99 %, respectively. Estimated prevalences of inadequacy for other micronutrients were low (0·1–2·2 %). Commonly consumed foods included maize, vegetable oil, tomatoes, rape leaves and small fish (>0·6 servings/d), whereas meat, eggs or dairy were rarely eaten (<0·2 servings/d). These findings suggest that the heavily plant-based diet of rural Zambian children provides inadequate Ca, folate, vitamin B12 and Fe to meet recommended nutrient intakes.